2020
DOI: 10.2147/ott.s256238
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel Circular RNA, circ_0005394, Predicts Unfavorable Prognosis and Contributes to Hepatocellular Carcinoma Progression by Regulating miR-507/E2F3 and miR-515-5p/CXCL6 Signaling Pathways</p>

Abstract: Objective: Circular RNAs (circRNAs) play a key role in cancer development and progression. Previously, circ_0005394 was found to be highly expressed in hepatocellular carcinoma (HCC) screened by circRNA microarray. However, the research with regard to the functions and mechanisms of circ_0005394 in HCC remains unknown. Materials and Methods: The expression of circ_0005394 in HCC was measured by qRT-PCR. The clinical relevance was evaluated by Fisher's exact test, Kaplan-Meier curves, and Cox regression model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Further, miR-323-3p can inhibit the apoptosis of human lung cancer cells and inhibit the invasion and metastasis of pancreatic ductal adenocarcinoma cells [ 55 , 56 ]. Moreover, miR-507 participates in the hsa_circ_0005394/miR-507/E2F3 axis and affects the process of hepatocellular carcinoma [ 57 ]. miR-330-5p can affect the expression of ELK1 and thus affect the proliferation, migration, and invasion of colon cancer cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, miR-323-3p can inhibit the apoptosis of human lung cancer cells and inhibit the invasion and metastasis of pancreatic ductal adenocarcinoma cells [ 55 , 56 ]. Moreover, miR-507 participates in the hsa_circ_0005394/miR-507/E2F3 axis and affects the process of hepatocellular carcinoma [ 57 ]. miR-330-5p can affect the expression of ELK1 and thus affect the proliferation, migration, and invasion of colon cancer cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically the effect was mediated by sponging of miR-507 and miR-515-5p to increase function of E2F Transcription Factor 3 (ETF3) and C-X-C motif chemokine ligand 6 (CXCL6). 75 circ_0009582, circ_0037120 and circ_0140117 circ_0009582, circ_0037120 and circ_0140117 were found to be useful markers of HCC in tumor tissue of patients with newly diagnosed HCC. Assay in plasma verified utility of the markers.…”
Section: Circrnas Implicated In the Etiology Of Hepatocellular Carcinmentioning
confidence: 97%
“… 123 , 124 , 127 In addition, relationships of circRNAs with mechanistic effects such as those resulting from sponging of miRs provided further corroboration. 64 , 75 , 126 Assay of circRNAs in peripheral blood mononuclear cells has also been investigated as an indirect method of detecting HCC. 120 Results from this study showed that circ_0000798 was a particularly useful indicator that also correlated with patients’ prognosis.…”
Section: Circrnas Implicated In the Etiology Of Hepatocellular Carcinmentioning
confidence: 99%
“…Sun et al. ( 35 ) demonstrate that circ_0005394 facilitates HCC growth via mediating the miR-507/E2F3 and miR-515-5p/CXCL6 axes. Jin et al.…”
Section: Role Of Circrna In Hccmentioning
confidence: 99%
“…CircRNA is highly tissue-specific and more stable than linear mRNA, making it a promising prognostic marker for HCC. Circ_0005394 is upregulated in HCC, and overexpression of circ_0005394 is linked with larger tumor size, more advanced TNM stages, and poorer survival outcome for HCC patients ( 35 ). An onco-circRNA, circMET, is identified to be an independent predictor of overall survival and postoperative recurrence in HCC patients ( 38 ).…”
Section: Clinical Significance Of Circrna In Hccmentioning
confidence: 99%